Botulinum toxin treatment of refractory vaginismus: a prospective study - Sejal Ajmera Desai, MD; Bela Shah, MD; George Kroumpouzos, MD, PhD (International Journal of Women's Dermatology)
Background:. Vaginismus is a common sexual dysfunction. A few studies have indicated that botulinum neurotoxin type A (BoNTA) can help treat refractory vaginismus by alleviating muscle tension. However, such studies did not use standardized methodology and BoNTA dosage. Objective:. The aim is to evaluate the efficacy of intravaginal BoNTA injection in treating refractory vaginismus. Also, we intended to assess the effectiveness and safety of modest doses, that is, 100 to 200 IU of submucosal BoNTA injections. Methods:. A prospective study was conducted in an outpatient surgical center over 18 months. Twenty patients aged 29 to 49 years (mean, 30.9 years) with refractory vaginismus were enrolled. All patients had been sexually inactive at the time of treatment. All participants had received various treatments such as psychotherapy, vaginal dilatator therapy, muscle relaxants, and lubricants with no relief. A dose of 100 to 200 IU of BoNTA was injected submucosally in the lateral sides of the bulbospongiosus, pubococcygeus, and puborectalis muscle areas. The patients were followed over 4 months posttreatment. Results:. Nineteen patients (95%) achieved satisfactory intercourse by the end of the 4-month follow-up period. A repeat BoNTA injection was not required as there were no recurrences. None of the participants reported adverse effects. Limitations:. A small sample size and lack of a control group. Conclusion:. Injecting submucosally modest BoNTA doses is an effective and safe treatment for refractory vaginismus. When conventional therapies fail, BoNTA can be used to lessen muscle contraction, alleviate pain, and facilitate dilator treatments. Our standardized protocol, which involves a careful submucosal injection technique, can minimize risks and make the procedure easy to perform for daily practice.